The Effect of Village Funds, Labor Force Participation Rate, and Average Years of Schooling on Per Capita Income in Underdeveloped Regions of Sumatra Island - Lionanta, Deffa; Taher, Taher (Lafadz Jaya Publisher, 2024)
This study analyzes the effect of Village Funds, the Labor Force Participation Rate (LFPR), and Average Years of Schooling (AYS) on per capita income in underdeveloped regions of Sumatra Island. Underdeveloped regions in Indonesia continue to face significant challenges in improving the welfare of their populations, with factors such as Village Funds, labor force participation, and education playing crucial roles in poverty alleviation. This research uses secondary data from Statistics Indonesia (BPS) and related institutions, employing regression analysis to examine the impact of these variables on per capita income. The results indicate that Village Funds and the Labor Force Participation Rate have a significant positive impact on per capita income, while Average Years of Schooling has a smaller but still significant effect. These findings provide valuable insights for policymakers in formulating development strategies aimed at improving welfare in underdeveloped areas. Approaches that involve more effective management of Village Funds, improving education quality, and enhancing labor force participation can serve as strategic steps to address economic disparities across regions in Sumatra Island.